Natural variation and artificial selection in four genes determine grain shape in rice. Issue 4 (16th August 2013) - Lu, Li; Shao, Di; Qiu, Xianjin; Sun, Liang; Yan, Wenhao; Zhou, Xiangchun; Yang, Lin; He, Yuqing; Yu, Sibin; Xing, Yongzhong
Summary: The size of cultivated rice ( Oryza sativa ) grains has been altered by both domestication and artificial selection over the course of evolutionary history. Several quantitative trait loci (QTLs) for grain size have been cloned in the past 10 yr. To explore the natural variation in these QTLs, resequencing of grain width and weight 2 ( GW2 ), grain size 5 ( GS5 ) and QTL for seed width 5 ( qSW5 ) and genotyping of grain size 3 ( GS3 ) were performed in the germplasms of 127 varieties of rice ( O. sativa ) and 10–15 samples of wild rice ( Oryza rufipogon ). Ten, 10 and 15 haplotypes were observed for GW2, GS5 and qSW5 . qSW5 and GS3 had the strongest effects on grain size, which have been widely utilized in rice production, whereas GW2 and GS5 showed more modest effects. GS5 showed small sequence variations in O. sativa germplasm and that of its progenitor O. rufipogon . qSW5 exhibited the highest level of nucleotide diversity. GW2 showed signs of purifying selection. The four grain size genes experienced different selection intensities depending on their genetic effects. In the indica population, linkage disequilibrium (LD) was detected among GS3, qSW5 and GS5 . The substantial genetic variation in these four genes provides the flexibility needed to design various rice grain shapes. These findings provide insight into the evolutionary features of grain size genes in rice.